Legal Responsibilities of Telepharmacy In Sales of Prescription Drugs In Indonesia - Milda, Nofi; Handar Subhandi Bakhtiar; Handoyo Prasetyo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The role of medication in healthcare services is crucial, but inappropriate use can endanger human health. Prescription drugs, including controlled substances, narcotics, and psychotropics, can only be dispensed by pharmacists based on a doctor's prescription at pharmaceutical service facilities in accordance with legal regulations to prevent misuse or abuse, which pose high health risks and can even be fatal. While the development of telepharmacy provides convenience for consumers in obtaining medications, it also introduces risks when prescription drugs are obtained without a doctor's prescription. This study aims to analyze the legal responsibilities of telepharmacy in the sale of prescription drugs and to understand the role of pharmacists in maintaining pharmaceutical standards within telepharmacy. Method: literature review sourced from Google Scholar. The Legal responsibility in Indonesian telepharmacy is governed by Government Regulations No. 71/2019 and No. 5/2021, Minister of Health Regulation No. 14/2021, Minister of Health Decree No. HK.01.07/MENKES/4829/2021, and BPOM Regulation No. 8/2020. Telepharmacy involves pharmacists, pharmacies, and electronic system operators, requiring adherence to service standards, data protection, and collaboration with conventional pharmacies. Therefore, regulations governing the pharmacy profession need to be updated to ensure telepharmacy services are safe and compliant with standards